A concern for falling impacts quality of life for people with a lower limb amputation. Issue 3 (27th June 2022) - Nugent, Kristin; Payne, Michael W.; Viana, Ricardo; Unger, Janelle; Hunter, Susan W.
Abstract : The purpose of this web-based survey study was to comprehensively evaluate subdomains of concern for falling and its association with quality of life (QoL) among people with lower-limb amputations (PLLA). Forty-eight adults (mean 61.8 ± 11.6 years) with a major (i.e. transtibial or transfemoral) amputation participated. Individuals were currently using a prosthesis for ambulation, completed a prosthetic rehabilitation program, had functional use of English and had access to an internet-connected device (e.g. laptop). Five standardized scales assessed a concern for falling: Modified Survey of Activities and Fear of Falling in the Elderly (mSAFFE), Activities-specific Balance Confidence (ABC) Scale, Prosthetic Limb Users Survey – Mobility (PLUS-M), Consequences of Falling Scale and Perceived Ability to Manage Falls Scale. QoL was evaluated using the WHO QoL-100 questionnaire. Spearman correlation analysis evaluated the relationship between the five concerns for falling scales. Five independent linear regression modeling evaluated the association of each concern for falling measure on QoL. Strong statistically significant correlations were found between mSAFFE and PLUS-M (rs  = −0.87; P  < 0.05). Three scales were significantly associated with QoL: mSAFFE [−1.16 (95% CI, −2.04 to −0.29)], ABC [0.36 (95% CI, 0.11–0.61)] and PLUS-M [0.50 (95% CI, 0.05–0.95)]. This is the first study to evaluate multiple concerns for falling subdomains among PLLA. Concern for falling should be addressed in prosthetic rehabilitation to improve community re-integration and QoL.